A Case Report of Isolated Bilateral Cerebral Peduncular Infarction. (31st July 2017) - Zhou, Chenguang; He, Yuanhong; Tian, Xiaorui; Chao, Zhiwen; Zhu, Yinghui; Cheng, Du; Li, Kui
Abstract : Isolated bilateral cerebral peduncular infarctions (BCPI) presenting as acute pseudobulbar palsy are rarely reported and, to the best of our knowledge, most of the previous reports of BCPI were related to locked-in syndrome and disturbance of consciousness. Herein, we described a case of a 55-year-old man who presented with acute pseudobulbar palsy and mild tetraparesis, but preserved eye movements, with no consciousness disturbance. DWI revealed an acute infarction involving the central portion of the cerebral peduncle with a characteristic "traditional Chinese eight character" sign. The relationship between the infarcted range in the cerebral peduncle and the clinical manifestation was discussed in our report.